2013
DOI: 10.1097/wno.0b013e31829c51f7
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Retinal Nerve Fiber Layer Thickness and Macular Volume Quantified by OCT in the North American Phase 3 Fingolimod Trial for Relapsing–Remitting Multiple Sclerosis

Abstract: Background Patients with multiple sclerosis (MS) demonstrate thinning of peripapillary retinal nerve fiber layer (RNFL) and decreased macular volume as measured by optical coherence tomography (OCT). To our knowledge, there are no previous reports from a large MS OCT database with strict quality control measures that quantitate RNFL and macula in patients with relapsing–remitting multiple sclerosis. Methods The University of California Davis OCT Reading Center gathered OCT data at baseline as part of the Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
6
17
1
Order By: Relevance
“…A rare 7% of these patients had reduced macular volume with normal pRNFL. 33 While this trial used the older time-domain version of OCT, other studies with spectral domain OCT have also reported approximately 10% of subjects having isolated macular thinning. 31,33 Another research group from Germany could not identify a similar phenotype in their cohort, however.…”
Section: Total Macular Volumesmentioning
confidence: 95%
See 2 more Smart Citations
“…A rare 7% of these patients had reduced macular volume with normal pRNFL. 33 While this trial used the older time-domain version of OCT, other studies with spectral domain OCT have also reported approximately 10% of subjects having isolated macular thinning. 31,33 Another research group from Germany could not identify a similar phenotype in their cohort, however.…”
Section: Total Macular Volumesmentioning
confidence: 95%
“…33 While this trial used the older time-domain version of OCT, other studies with spectral domain OCT have also reported approximately 10% of subjects having isolated macular thinning. 31,33 Another research group from Germany could not identify a similar phenotype in their cohort, however. 34 Decreased macular volumes are associated with decreased visual function, reduced brain volumes, and disability scores in patients with MS. 35 Baseline macular volume has been shown to predict 10-year disability in MS patients, demonstrating significant relevance for prognosis.…”
Section: Total Macular Volumesmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the usefulness of RNFL for monitoring disease progression and neurodegeneration longitudinally in MS clinical trials is not well established. Recently, baseline RNFLT and macular volume data from the prospective longitudinal phase 3 fingolimod trial were published . A potential criticism of our study is that PRVEP latency, visual acuity and LCLA data were not available.…”
Section: Discussionmentioning
confidence: 93%
“…The University of California Davis Reading Center recently published the results of Stratus (TD) OCT quality control in 2 multicenter MS clinical trials (40). The University of California Davis Reading Center recently published the results of Stratus (TD) OCT quality control in 2 multicenter MS clinical trials (40).…”
Section: Oct In Clinical Trials: Role For Reading Centersmentioning
confidence: 99%